Comparison of Insulated Switch Gear with Desiccant Addition to SF6 Gas Quality System at Waru Substation - Anggara Trisna Nugraha; Moch Fadhil Ramadhan; Muhammad Jafar Shiddiq; Muhammad Fikri Fathurrohman (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2023)
In electrical instrumentality with SF6 gas insulation, the quality of SF6 gas in line with the standard is prime to wise insulation power, if there' a decrease in gas quality, there'll even be a decrease among the number of voltage insulation on electrical equipment. throughout this case, it had been found that the quality of SF6 gas was deteriorating within the Ganz whole GIS Compartment at the Waru Substation Substaction, specifically the position level of the SF6 isolation gas that exceeded the required standard limit. Besides, this GIS isn't equipped with silica gel/desiccant as a condition gripping material and gas sorbent material from amendment PMT (IEEE Std 11251993) that ends throughout a decrease among the standard of SF6 gas. The addition of drier among the GIS is needed to keep up the quality of SF6 gas. These materials are analyzed for quantity and performance once applied within the compartment therefore as that deterioration of the quality of SF6 gas and thus the prevalence of insulation failure is avoided as early as possible, and SF6 remains in its characteristics with a BDV of 78.6 kV/cm (according to SF6 crucial Breakdown Volatge). And it hoped that SF6 gas will add line with it operate as a decent insulating medium. As degree application, a drier experiment has been administered among the GIS compartment at the Waru Substation station